A Multiple-Level DCT Based Robust DWT-SVD Watermark Method - Xueyi Ye; Xueting Chen; Meng Deng; Shuyun Hui; Yunlu Wang (2014 Tenth International Conference on Computational Intelligence and Security, 2014)
The contradiction between the capacity and the robustness of image watermark has not been solved in the digital watermark research. In this paper, a robust Discrete Wavelet Transform (DWT) - Singular Value Decomposition (SVD) watermark method based on multiple-level Discrete Cosine Transform (DCT) is proposed by the advantage of DCT's energy concentration. Firstly, the carrier image is done discrete wavelet transform and its low frequency sub-band is obtained. Secondly, the coefficient matrix of the low frequency sub-band is partitioned. Then each block is done multiple-level DCT. Thirdly, according to the capacity of the embedded watermark, the appropriate DCT coefficients are selected in each block to form a new matrix, and then the encrypted watermark is embedded in the singular value matrix of the new matrix. Finally, the image containing watermark is obtained by SVD synthesis, multiple-level inverse DCT and multiple-level inverse DWT. Experimental results show that compared with other similar watermark methods, this paper's method not just can embed the large-capacity watermark by dynamically selecting the appropriate DCT coefficients, but also has robustness to different image attacks.